Outcomes following ABO-incompatible kidney transplantation performed after desensitization by nonantigen-specific immunoadsorption - Becker, Luis Eduardo; Siebert, Daniela; Süsal, Caner; Opelz, Gerhard; Leo, Albrecht; Waldherr, Rüdiger; Macher-Göppinger, Stephan; Schemmer, Peter; Schäfer, Sebastian Markus; Klein, Katrin; Beimler, Jörg; Zeier, Martin; et al. (Transplantation, 2015)
Background - For desensitization of ABO-incompatible kidney transplant recipients we recently proposed nonantigen-specific immunoadsorption (IA) and rituximab. - Methods - We now compared clinical outcomes of 34 ABO-incompatible living-donor kidney recipients who were transplanted using this protocol with that of 68 matched ABO-compatible patients. In addition, we analyzed efficacy and cost of nonantigen-specific as compared to blood group antigen-specific IA. -Results - Before desensitization, the median isoagglutinin titer of 34 ABO-incompatible patients was 1:64 (Coombs technique). Patients received a median of 7 preoperative IA treatments. Twenty-four patients had a median of 2 additional plasmapheresis treatments to reach the preoperative target isoagglutinin titer of 1:8 or less. After a median postoperative follow-up of 22 months, overall graft survival in the ABO-incompatible group was not significantly different from that in ABO-compatible patients (log-rank P = 0.20), whereas patient survival tended to be lower (log-rank P = 0.05). The incidence of rejection episodes was 15% in both groups. The ABO-incompatible kidney recipients had a higher incidence of BK virus replication (P = 0.04) and nephropathy (P = 0.01) and showed more often colonization with multidrug resistant bacteria (P = 0.02). In comparison to blood group antigen-specific IA, nonantigen-specific IA showed equal efficacy but was associated with reduction in cost. - Conclusions - Clinical outcomes of ABO-incompatible patients desensitized with a nonantigen-specific IA device and rituximab do not differ from that of matched ABO-compatible patients although a trend toward reduced patient survival was noted. Special attention must be paid to the higher incidence of BK virus infection in recipients of ABO-incompatible grafts.